Ionic liquid-polymer composites: a new platform for multifunctional applications - Correia, D. M. (2020)
Ionic liquids (ILs) have emerged as a novel class of chemical compounds for the development of advanced (multi)functional materials with outstanding potential in applications of several areas due to the ILs unique properties and functionalities. The combination of ILs with polymers, in a composite, allows developing smart materials, which synergistically combine the features of specific polymers and ILs. Moreover, ILs can be extensively modified by the incorporation of functional groups with specific properties into the cation, anion or both. Thus, it is possible to tune the IL, the polymer, or both to obtain a broad spectrum of multifunctional composites and address the specific requirements of many applications. This work focusses on advanced materials and strategies concerning ILs and polymers for the development of smart IL/polymer-based materials for applications including responsive and sensitive sensors, actuators, environment, batteries, fuel cells, biomedical applications, among others.